Evaluation of the Mechanical Properties of Hydraulic Concrete Reinforced with Recycled Polyethylene Terephthalate - Durán, Hernán José Hernández (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study evaluates the mechanical properties of hydraulic concrete reinforced with recycled Polyethylene Terephthalate (PET) plastic fibers, addressing both construction performance and environmental sustainability. While concrete is a widely used material for its strength and durability, the increasing production and disposal of PET waste present significant ecological challenges. Incorporating recycled PET fibers into hydraulic concrete offers a dual benefit: reducing plastic waste while potentially improving the material’s mechanical performance. Despite prior research on plastic additives in concrete, limited attention has been given to the specific mechanical behavior of hydraulic concrete reinforced with recycled PET fibers. The main objective of this research is to analyze the effect of PET fiber incorporation on compressive strength through controlled laboratory experiments. Concrete mixes with varying fiber proportions were prepared and subjected to compressive strength testing, with results compared to standard concrete performance. Beyond technical evaluation, the study also situates its findings within the framework of the Sustainable Development Goals (SDGs), highlighting PET recycling as a strategy for advancing sustainable construction and waste management. The results are expected to inform the development of more sustainable and efficient concrete formulations while contributing to broader environmental conservation efforts.